Zen and the magic of photography learning to see and to be through photography - Rowe, Wayne; Safari eBooks (Santa Barbara, Calif. : Rocky Nook ; Sebastopol, Calif. : Distributed by O'Reilly Media, 2010)
"Zen and the Magic of Photography geared toward helping photographers develop their visual awareness, sensitivity, and intuition. It is designed to improve the quality of your photography by helping you to discover, create, and capture the points of intersection and merging between photography and Zen; between camera and "real moments"; between seeing and being. This is the point at which all such distinctions no longer exist, the point at which photography and Zen are one. This is the point at which we discover and create our best photographic images"--Resource description page.
Description based on print version record.
Includes bibliographical references (p. 92-94).
Keywords: Photography -- Psychological aspects; Composition (Photography); Electronic books